P377 CHALLENGING RISK STRATIFICATION IN BRUGADA SYNDROME: A CASE OF VENTRICULAR TACHYCARDIA IN A LOW–RISK PATIENT. (18th May 2022) - Marcon, L; Zannoni, J; Tundo, F; Moltrasio, M; Majocchi, B; Fassini, G; Riva, S; Casella, M; Tondo, C; Ribatti, V
Abstract: A 22–year–old healthy athlete was referred to our hospital for electrocardiographic findings consistent with intermittent type–1 Brugada pattern. A routine electrocardiogram (ECG) performed during a check–up showed sinus rhythm, normal PR interval and QRS duration, rSR' with a coved type ST–segment elevation in V2 lead (Figure 1 ).The patients denied history of syncope or palpitations and his family history did not show sudden cardiac death or Brugada syndrome (BrS). Transthoracic echocardiography was normal and a 12–lead Holter monitoring revealed the intermittence of the type–1 Brugada pattern. The patient was hospitalized for further investigation. On admission, ECG showed a type–2 Brugada pattern; therefore, Ajmaline challenge test (1 mg/kg injection in 10 minutes) was performed and resulted positive. Subsequently, the patient underwent an electrophysiological study (EPS) which was negative for induction of sustained arrhythmias. The protocol adopted consisted of double extrastimuli programmed electrical stimulation until refractoriness (drive 600/220 ms and 400/210 ms), at double sites (right ventricle apex and right ventricular outflow tract). Furthermore a genetic test was performed using next–generation sequencing, showing a heterozygous mutation in the SCN5A gene, encoding for sodium channel alpha subunit (variant c.5363delA), not previously described in the literature. Since the low arrhythmic risk, the patient was implanted with a loop recorder (ILR, Medtronic Reveal LINQ), entering a program of home monitoring. After a 15–months follow–up, an episode of ventricular polymorphic tachycardia lasting 2 minutes and 11 seconds, associated with lightheadedness and palpitations, was detected by the remote monitoring (Figure 2 ). The patient was therefore hospitalized. During the in–hospital stay a cardiac magnetic resonance was performed to exclude other underlying diseases, identifying an enlarged right ventricle (EDVi 114 ml/m2) and abnormal free wall motion (Figure 3 ), thus reaching one major criteria of arrhythmogenic cardiomyopathy (however not sufficient for the diagnosis). The patient was then implanted with a subcutaneous implantable cardiac defibrillator (Boston Scientific EMBLEM MRI S–ICD). We presented a case of complex arrhythmic risk stratification in a possible overlap of an arrhythmogenic cardiomyopathy and a Brugada Syndrome in a young athlete who experienced a sustained ventricular tachycardia during loop–recorder monitoring.